INVESTIGATING MICROANGIOPATHY USING SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY IN PATIENTS WITH SUSAC SYNDROME. Issue 10 (October 2021) - Wirth, Magdalena A.; Khan, Haaris M.; Chan, Jillian; Carruthers, Robert; Lo, Julian; Sarunic, Marinko V.; Navajas, Eduardo V.; Sheldon, Claire A.
Abstract : Purpose: To determine whether optical coherence tomography angiography is of diagnostic utility for Susac syndrome (SuS) by quantifying microvascular retinal changes. Methods: We enrolled 18 eyes of 9 healthy controls and 18 eyes of 9 patients with chronic SuS (12 had previous branch retinal artery occlusions and 6 were clinically unaffected). Images of the fovea were taken using an optical coherence tomography angiography system. Analysis included vessel density, fractal dimension, vessel diameter, and measurements of the foveal avascular zone (area, eccentricity, acircularity index, and axis ratio) in deep and superficial retinal layers. Results: Skeleton density and inner ring vessel density were significantly lower in patients with SuS (skeleton density: Susac 0.11 ± 0.01 vs. controls 0.12 ± 0.01, P = 0.027. VD: SuS 0.39 ± 0.04 vs. controls 0.42 ± 0.02, P = 0.041). Eccentricity and axis ratio were significantly higher in patients with SuS (EC: Susac 0.61 ± 0.11, controls 0.51 ± 0.10, P = 0.003; axis ratio: Susac 1.57 ± 0.28, controls 1.39 ± 0.11, P = 0.005). SuS eyes (affected and unaffected) had poorer outcomes of the remaining vascular parameters compared with controls ( P > 0.05). Conclusion: Optical coherence tomography angiography identified chronic microvascular changes in the eyes of patients with chronic SuS. Even clinically unaffected SuS eyes showed poorer vascular parameters. Although further research is needed, this noninvasive imaging modality seems to have the potential to serve as a valuable additive diagnostic tool. Abstract : Our study found microvascular alterations in the superficial and deep vascular plexuses of the retinal vasculature in patients with chronic Susac syndrome compared with healthy controls. Optical coherence tomography angiography may contribute to the diagnostic armamentarium as a valuable noninvasive tool that detects subclinical retinal microvascular changes in Susac syndrome.